Maxillonasal dysplasia (Binder's syndrome) and its treatment with costal cartilage graft: A follow-up study - Yogesh C. Bhatt; Kinnari A. Vyas; Mangesh S. Tandale; Nikhil S. Panse; Harpreet S. Bakshi; Rajat K. Srivastava (Indian Journal of Plastic Surgery)
Maxillonasal dysplasia or Binder's syndrome is an uncommon congenital condition characterized by a retruded mid-face with an extremely flat nose. We report here six patients with maxillonasal dysplasia whose noses were corrected with onlay costal cartilage grafts using a combined oral vestibular and external rhinoplasty approach for nasal dorsal augmentation, columellar lengthening, and premaxillary augmentation. The cartilage graft was dipped in a solution of 100 ml 0.9% NaCl and one vial (80mg) gentamicin for 30 min to prevent warping. L struts made for nasal augmentation, columellar lengthening, and premaxillary augmentation were fixed to one another by slots made in the graft. This technique has been used in children, adults, and for secondary cases with promising results. All patients were of class I dental occlusion. The nasal and premaxillary augmentation which was monitored by serial photography was found to be stable over a follow-up period of three years.